Role of the Chinese culture in modern development of the People’s Republic of China - Сaғынбек М.; Арзыкулов, А. А. (Journal of Oriental Studies, 2018)
In article authors consider the place of modern Chinese culture, her feature in modern Chinese society and her prospects of development. This question was also considered during ХІХ of the National Congress of the Communist Party of China. According to the statement of the Chinese President Xi Jingping, China has to become not only the economic, but also cultural new power. If to consider the fact that the Chinese culture plays a large role in carrying out the Chinese policy of “soft power” it is possible to tell confidence that the Chinese leaders will pay much attention on this branch.